The Effect of Reinforcement Surface Treatment With Citric Acid on The Flexural and Hardness Properties of Epoxy/Wood Sawdust Composites - I Wayan Padma Yogi Asana; Risa Nurin Baiti; Komang Widhi Widantha (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
This study investigates the effect of citric acid surface treatment on wood sawdust used as reinforcement in epoxy-based composites, with a focus on improving bending strength. Wood sawdust was subjected to surface modification using citric acid and sodium hydroxide (NaOH) under equivalent molar concentrations. Bending strength tests showed that both citric acid and NaOH treatments significantly improved mechanical performance compared to untreated samples, with average strengths of 33.83 MPa and 32.82 MPa, respectively, versus 21.83 MPa for the untreated group. Statistical analysis was conducted to compare the two treatments. After confirming normal distribution but unequal variances, a Welch two-sample t-test was performed, yielding a p-value of 0.742. This result indicates no statistically significant difference in bending strength between citric acid and NaOH treatments.